Understanding the anaerobic biodegradability of food waste: Relationship between the typological, biochemical and microbial characteristics. (1st March 2017) - Fisgativa, Henry; Tremier, Anne; Le Roux, Sophie; Bureau, Chrystelle; Dabert, Patrick
Abstract: In this study, an extensive characterisation of food waste (FW) was performed with the aim of studying the relation between FW characteristics and FW treatability through an anaerobic digestion process. In addition to the typological composition (paper, meat, fruits, vegetables contents, etc) and the physicochemical characteristics, this study provides an original characterisation of microbial populations present in FW. These intrinsic populations can actively participate to aerobic and anaerobic degradation with the presence of Proteobacteria and Firmicutes species for the bacteria and of Ascomycota phylum for the fungi. However, the characterisation of FW bacterial and fungi community shows to be a challenge because of the biases generated by the non-microbial DNA coming from plant and by the presence of mushrooms in the food. In terms of relations, it was demonstrated that some FW characteristics as the density, the volatile solids and the fibres content vary as a function of the typological composition. No direct relationship was demonstrated between the typological composition and the anaerobic biodegradability. However, the Pearson's matrix results reveal that the anaerobic biodegradation potential of FW was highly related to the total chemical oxygen demand (tCOD), the total solid content (TS), the high weight organic matter molecules soluble in water (SOLW >1.5 kDa) and the C/N ratio content. These relations may help predicting FW behaviour through anaerobic digestion process. Finally, this study also showed that the storage of FW before collection, that could induce pre-biodegradation, seems to impact several biochemical characteristics and could improve the biodegradability of FW. Highlights: An extensive experimental characterisation of food waste (FW) is proposed. Constituents analysis explains some physicochemical FW characteristics variations. FW contain interesting fungi and yeast that enhance biodegradability. Correlations between FW characteristics may help predict performance of anaerobic digestion. Storage of FW before collection affects its biodegradability.